ChemInform Abstract: Expedient and Efficient One Pot Synthesis of Trifluoroethyl Ethers from Metal Free 2, 4, 6‐Tris‐(2, 2, 2‐trifluoro‐ethoxy)‐[1, 3, 5] Triazene. Issue 34 (August 2015) - Mangawa, Shrawan Kumar; Sharma, Chiranjeev; Kumar Singh, Ashawani; Awasthi, Satish K.
Abstract Various fluorinated alkyl and aryl ethers are eco‐friendly obtained using the synthetic non‐toxic, non‐ozone depleting, and stable 2, 4, 6‐tris‐(2, 2, 2‐trifluoroethoxy)‐[1, 3, 5]triazene (II) as trifluoroethylation reagent.